Erosive Wear and Corrosion in Hydrogenated and Silicon DLC Film Deposited on Carbon Steel - A. H. S. Bueno; J. Solis; H. Zhao; C. Wang; T. A. Simões; C. E. V. Masalla; A. Malacarne; R. C. Souza; R. M. D. Brydson; R. Barker; A. Neville (Materials Research)
Amongst numerous traditional coatings to protect internal surfaces, Diamond-Like Carbon (DLC) films attract significant interest from many industries, due to the ability of these coatings to overcome the toxic and/or environmentally unfriendly aspects of some common deposition techniques, especially electroplating. In addition, DLC coatings can be used to reduce corrosion, wear and importantly, abrasion on the inside of components, providing improved efficiency and prolonged lifetime. This work evaluates the performance of hydrogenated and silicon DLC coatings deposited by Plasma-Enhanced Chemical Vapour Deposition (PECVD) on carbon steel in terms of their erosion and electrochemical corrosion resistance. Erosion studies were conducted in a saline solution under different velocities and sand concentrations - modelling the direct impingement of high velocity, sand-laden fluid encountered in multiphase equipment flow. These experiments showed that for all impingement velocities, the Si-DLC exhibited lower mass loss. This coating enhanced integrity against erosion-corrosion acting together under saline environments with sand. The enhanced resistance was attributed to improved ductility of the surface layer, as well as the generation of an effective corrosion barrier which reduced pitting corrosion and suppressed significantly the anodic reaction.